(untitled) (Comprehensive Journal of Science, 2025)
The withdrawal of an administrative decision refers to its complete nullification along with all its legal effects, not only prospectively but also retroactively from the date of its issuance. Withdrawal is one of the mechanisms employed by the administrative authority to rectify decisions that are unlawful, in adherence to the principle of legality. It also serves to protect the administration from potential legal challenges against such decisions before the judiciary. Consequently, the withdrawal strips the decision of its legal force with retroactive effect, eliminating all of its consequences. This is intended to ensure the stability of individuals’ legal positions, which must not be undermined.